QOL-06. PREDICTING VENOUS THROMBOEMBOLISM IN PATIENTS WITH ADULT-TYPE DIFFUSE GLIOMAS. (14th November 2022) - Burdett, Kirsten B; Unruh, Dusten; Drumm, Michael; Lamano, Jonathan; Schwartz, Margaret; Chandler, James; Javier, Rodrigo; Steffens, Alicia; Amidei, Christina; Lipp, Eric S; Peters, Katherine B; Lai, Albert; et al.
Abstract: Venous thromboembolism (VTE) is a common paraneoplastic complication in patients with adult-type diffuse gliomas. VTE greatly diminishes quality-of-life, and can even be life-threatening. While effective VTE prediction models exist for other cancers, those models do not work for gliomas. Thus, there are no standard guidelines for thromboprophylaxis in glioma patients. To address this deficiency, arterial blood, tumor tissue, and comprehensive clinical-pathologic data (including next generation sequencing) were obtained from 258 newly diagnosed WHO grade 2-4 adult-type diffuse glioma patients at Northwestern Memorial Hospital. Forty-six out of 258 grade 2-4 glioma patients (17.8%) experienced a subsequent VTE. Intratumoral expression of two proteins that have been associated with VTE risk in other cancers, thromboplastin and podoplanin, was higher in IDH wild-type than IDH mutant gliomas. Tissue expression of both markers was associated with increased VTE risk, but in the circulation, only thromboplastin positively correlated with VTE. LASSO time-to-event analysis showed that older patient age, elevated body mass index, elevated WBC count, hypertension, a preoperative history of VTE, asthma, and higher WHO grade predicted increased postoperative VTE risk, whereas hypothyroidism, IDH mutation, and MGMT promoter methylation were negative risk factors. Together, these 10 variables generated a receiver operating characteristic curve for 3, 6, 9, and 12 months from original surgery resulting in estimated AUC value of 0.82 in the Northwestern discovery cohort, 0.72 in the UCLA validation cohort (N=68), and 0.68 in the Duke validation cohort (N=157). We created an online prediction tool based on this model, which estimates VTE risk up to 1 year from original surgery. To the best of our knowledge, this is the first externally validated VTE risk prediction tool designed specifically for adult-type diffuse glioma patients. This tool, based on readily obtainable information, provides treating physicians with more objective risk estimates on which to base thromboprophylaxis decision-making.